Peran Etika Bisnis Terhadap Kepercayaan Konsumen - Hasna Lutfi Indriani; Ulviana Agustina; Ulya Triana Dahar; Agustiawan Agustiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Business ethics is a business approach to conducting operations that covers all aspects of society, business and the public. Business ethics in an organization can influence the values, norms, and behavior of leaders and staff. Consumer trust is the confidence that consumers have in a product, service, or brand. This belief has an important role in influencing consumers' decisions to buy, reuse, and recommend certain products and services. CSR is a business initiative to consider the concerns of many stakeholders, including the environment, society, workers, and customers. The purpose of this research is to find out how important company ethics is in building consumer trust. This research uses a qualitative descriptive analysis method and data is obtained from literature studies, several books, references on the internet, and journals that examine similar research to support research on